Handbook of research on decision-making techniques in financial marketing - Dinçer, Hasan; Yüksel, Serhat (IGI Global, 2019)
Consumer needs and demands are constantly changing. Because of this, marketing science and finance have their own concepts and theoretical backgrounds for evaluating consumer-related challenges. However, examining the function of finance with a marketing discipline can help to better understand internal management processes and compete in today's market. The Handbook of Research on Decision-Making Techniques in Financial Marketing is a collection of innovative research that integrates financial and marketing functions to make better sense of the workplace environment and business-related challenges. Different financial challenges are taken into consideration while many of them are based on marketing theories such as agency theory, product life cycle, and optimal consumer experience. While highlighting topics including behavioral financing, corporate ethics, and Islamic banking, this book is ideally designed for financiers, marketers, financial analysts, marketing strategists, researchers, policymakers, government officials, academicians, students, and industry professionals.
Keywords: Financial Marketing; Decision-Making Techniques; Handbook